Modeling and simulation of interaction between light sources and living biological tissues - Çitkaya, Ahmet Yasin. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
The assessment of exposure level due to commonly used light sources needs specific attention in today's technology of lighting. The main reason behind this concern is that if exposure levels are not known, the biological implications and necessary safety limits cannot be determined accurately. In this regard, this thesis study has aimed to design, implement, analyze and solve partial differential equations related to thermal response of biological tissue which is subject to optical radiation. This thesis, however, is not limited to the numerical models for analysis of tissue thermal response under different light sources. The validation of the implemented mathematical algorithm is obtained via in-vitro experiments. Examining the most powerful factors in light-tissue interaction has made it possible to investigate each parameter by variations and their induced outputs. Accompanying the theoretical and numerical validation, this dissertation has enlarged its scope with in-vivo experiments for providing reference data to scientific research in the literature and medical application development for safer lighting designs..
Keywords: Tissues -- Innervation.